Health-Based Pre-Marital Education for Adolescent Reproductive Health and Family Readiness: Edukasi Kesehatan Pra-Nikah Berbasis Kesehatan untuk Kesiapan Reproduksi Remaja dan Kesiapan Berkeluarga - Dzulqarnain Andira (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Adolescent reproductive health is a critical determinant of future family well-being and national human capital quality. Adolescents are prepared with critical information by pre-marital health education to make thoughtful judgments about their physical, mental, and social preparedness for marriage. Context: In many Indonesian communities, teenagers are increasingly exposed to hazardous activities, but there is still little access to organized, evidence-based health education prior to marriage. Targeted interventions are necessary for high school pupils, who are in a transitional age group, to close this knowledge difference. There is a knowledge gap since there aren't many community-based educational initiatives that have specifically concentrated on providing senior high school students in the Porong, Sidoarjo region with thorough pre-marital health education—which covers Islamic viewpoints, mental readiness, and reproductive health. Goals: This community service endeavor sought to raise teenagers' awareness of premarital health readiness, including reproductive health, risk prevention, and family preparedness, within the framework of Islamic values. Results: The activity, which involved interactive lectures and discussions with 12th-grade students from SMA Kemala Bhayangkari 3 Porong, enhanced participants' understanding of reproductive health, consciousness of the dangers of pre-marital sexual behavior, and awareness of the value of physical, mental, and social preparation prior to marriage. This program is unique in that it combines thorough pre-marital health education with Islamic ethical principles in a community service program at the high school level. It specifically addresses the medical, psychological, and spiritual aspects of family preparation. Implications: The findings indicate that health-based pre-marital education can serve as a promotive and preventive approach in adolescent populations to support healthier family formation and reduce reproductive health risks. Highlights: Twelfth-grade participants demonstrated greater understanding of reproductive risks and responsible decision-making. Interactive lectures and open discussions addressed physical, psychological, social, and spiritual dimensions. Learners valued practical guidance on examinations, peer pressure, schooling, careers, and marriage planning. Keywords: Pre-Marital Health, Adolescent Reproductive Health, Family Readiness, Community Service, Islamic Values, Health Education